Government Roles and Public Investment Strategies in Economic Development - Beisengaliyev Berik; Shynar Isabekovna Kossymbayeva (SHS Web of Conferences)
This study examines the evolution of government participation in the economy, analyzing key theoretical approaches and strategic directions of public investment. The research explores contrasting views from classical liberalism, advocating minimal state intervention, to Keynesian and neo-institutional perspectives that emphasize government regulation for economic stability and social equity. The findings highlight the role of public investment in infrastructure, environmental sustainability, innovation, and social programs, illustrating successful policies across different economies. A major gap identified is the lack of a universal framework for optimizing public investment while balancing economic growth and market efficiency. The study underscores the implications of government intervention in fostering long-term economic resilience and addressing market failures. Future research should focus on integrating institutional adaptability with strategic public investment models to enhance policy effectiveness.